Covalent Organic Framework Membranes for Selective Ion Separation - Zhang, Hao; Xu, Fangyuan; Lin, Zhimin (International Journal of Materials Science and Technology Studies, 2026)
The escalating global urgency for clean water and critical mineral recovery necessitates separation technologies that transcend the inherent permeability-selectivity trade-offs of conventional polymeric membranes. Covalent Organic Frameworks (COFs), distinguished by their precise reticular chemistry, tunable pore architectures, and modular functionality, have emerged as a transformative platform for next-generation ion separation. This review systematically evaluates recent breakthroughs in the engineering of COF-based membranes, focusing on the nexus between fabrication strategies and application performance. We critically examine diverse synthesis methodologies, including interfacial polymerization, in situ growth, and electrophoretic deposition, highlighting how these techniques control membrane crystallization and defect minimization. Furthermore, the review details the deployment of these materials across three pivotal sectors: seawater desalination, where they achieve superior salt rejection; lithium resource extraction, enabling high-precision Li+/Mg2+ differentiation; and the purification of drinking water from heavy metals and radionuclides. The discussion concludes by identifying the critical bottlenecks in scalability and long-term stability that must be addressed to transition COF membranes from laboratory prototypes to industrial implementation.